Abscessed retroperitoneal hematoma as a late complication of adrenalectomy: a case report. - Carrillo - Barraza , S.; De la Cruz - Rivera, D.S (Revista de Ciencias Médicas Torreón, 2026)
Retroperitoneal hematoma is an uncommon complication following adrenalectomy; however, its progression to abscess represents a potentially life-threatening condition associated with high morbidity and mortality when diagnosis and treatment are delayed. Clinical presentation is often nonspecific, including fever without an identifiable source, abdominal or flank pain, and systemic inflammatory response, which may delay early recognition. Predisposing factors include recent surgical procedures, persistent undrained collections, and immunocompromised states, particularly in oncologic patients. Diagnosis relies on clinical suspicion supported by imaging studies, with computed tomography being the modality of choice to identify retroperitoneal collections and signs of infection. Treatment depends on the patient’s clinical condition and characteristics of the collection, requiring broad-spectrum antibiotic therapy and, in most cases, percutaneous or surgical drainage. We present the case of a 76-year-old male with a history of right nephrectomy for metastatic clear cell renal carcinoma and adrenalectomy, who developed left retroperitoneal collections suggestive of abscess, requiring specialized hospital management.